2019
DOI: 10.1093/aje/kwz268
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Utility of Coarsened Exact Matching for Pharmacoepidemiology Using Real and Simulated Claims Data

Abstract: Coarsened exact matching (CEM) is a matching method proposed as an alternative to other techniques commonly used to control confounding. We compared CEM with 3 techniques that have been used in pharmacoepidemiology: propensity score matching, Mahalanobis distance matching, and fine stratification by propensity score (FS). We evaluated confounding control and effect-estimate precision using insurance claims data from the Pharmaceutical Assistance Contract for the Elderly (1999–2002) and Medicaid Analytic eXtrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 48 publications
2
44
0
Order By: Relevance
“…Further, we sought to match a discrete list of static covariates available at baseline that reflect key risk factors associated with mortality in COVID‐19. CEM is expected to produce high performance relative to other matching options in this scenario 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we sought to match a discrete list of static covariates available at baseline that reflect key risk factors associated with mortality in COVID‐19. CEM is expected to produce high performance relative to other matching options in this scenario 35 …”
Section: Discussionmentioning
confidence: 99%
“…CEM is expected to produce high performance relative to other matching options in this scenario. 35 This study also has its limitations. First, given this is a large cohort retrospective study, data were collected from EHR systems, which precluded the level of detail possible with a manual medical chart review.…”
Section: F I G U R Ementioning
confidence: 91%
“…CEM also meets the congruence principle, with the data space and analysis space being the same, and reduces model dependence (Blackwell et al 2010). Studies with both real and simulated data, moreover, have shown that CEM is superior to other matching methods in regards to achieving the best balance (Fullerton et al 2016;Iacus et al 2012;King and Nielsen 2019;Ripollone et al 2020). Furthermore, CEM is considered most appropriate to use when the covariates include both continuous and discrete variables as well as so-called mixed variables, i.e., continuous variables with natural breakpoints (King and Nielsen 2019), such as is the case with the various couple differentials.…”
Section: Empirical Strategymentioning
confidence: 88%
“…CEM, as outlined above, comprises four basic steps: first, the covariates are coarsened; second, exact matching is implemented with the coarsened data; third, unmatched units in bins that do not contain units of the opposite exposure status, i.e., treatment or control, are eliminated; finally, SATT is estimated using the matched dataset (Ripollone et al 2020). We now, in turn, discuss our approach to each step.…”
Section: Empirical Strategymentioning
confidence: 99%
“…This matching procedure can produce a more balanced match than other strategies, 31 and when compared to traditional propensity score matching reduces bias when less than 10 strong confounders need to be matched. 33 A detailed description of this procedure has been described elsewhere. 32 Patients were matched on identified confounders: age, sex, year of diagnosis, SEER registry region, Charlson score category (0, 1, 2, 3þ), receipt of care at a teaching hospital, and survival time from diagnosis to death.…”
Section: Matching Proceduresmentioning
confidence: 99%